2023
DOI: 10.1021/acs.jpclett.3c00212
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Chemical Changes Causing Transient Potential Patterns during Cobalt Electrodeposition: An Operando SHINERS Investigation

Abstract: Transient potential oscillations in a self-organized system involve a sequence of mass-transfer-limited chemical reactions. Often, these oscillations determine the microstructure of the electrodeposited metallic films. In this study, two distinct potential oscillations have been observed during galvanostatic deposition of cobalt in the presence of butynediol. Understanding the underlying chemical reactions in these potential oscillations is essential for designing efficient electrodeposition systems. Operando … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For the sake of clarity, a single potential oscillation is considered (Figure A). The single oscillation can be segmented into four regions, as observed in our previous operando SHINERS study of cobalt electrodeposition with butynediol A n –B n region: Proton reduction to adsorbed hydrogen takes place on CoNi by the following Volmer step. CoNi + H false( aq false) + + e CoNi H ad goodbreak0em1em⁣ ( Volmer step ) The Heyrovsky step is not possible at low overpotentials as the M–H bond (where M = Co, Ni) is very stable.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…For the sake of clarity, a single potential oscillation is considered (Figure A). The single oscillation can be segmented into four regions, as observed in our previous operando SHINERS study of cobalt electrodeposition with butynediol A n –B n region: Proton reduction to adsorbed hydrogen takes place on CoNi by the following Volmer step. CoNi + H false( aq false) + + e CoNi H ad goodbreak0em1em⁣ ( Volmer step ) The Heyrovsky step is not possible at low overpotentials as the M–H bond (where M = Co, Ni) is very stable.…”
Section: Resultsmentioning
confidence: 96%
“…Our study revealed that the strongly adsorbed intermediate, viz., Co–H, during the electrodeposition of cobalt led to the suppression of current, resulting in the NDR, where the adsorbed hydrogen can be scavenged by butynediol as a result of its hydrogenation, leading to electrochemical potential oscillation . Our operando SHINERS-Raman investigation provided insights regarding the involvement of cobalt hydroxide formation/dissolution for the observation of oscillation in addition to adsorbed hydrogen formation/removal …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation